2017
DOI: 10.1016/j.cell.2017.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Landscape in Early Lung Adenocarcinoma by Paired Single-Cell Analyses

Abstract: Summary To guide the design of immunotherapy strategies for patients with early stage lung tumors, we developed a multiscale immune profiling strategy to map the immune landscape of early lung adenocarcinoma lesions to search for tumor-driven immune changes. Utilizing a barcoding method that allows a simultaneous single cell analysis of the tumor, non-involved lung and blood cells together with multiplex tissue imaging to assess spatial cell distribution, we provide a detailed immune cell atlas of early lung t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

69
914
3
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 990 publications
(991 citation statements)
references
References 64 publications
69
914
3
5
Order By: Relevance
“…These cells are likely responsible for IFNg secretion, the most powerful PD-L1 stimulating factor (45). Secondly, KRAS mutation was associated with a reduced expression of PD-L1, as previously documented (44), while, at variance with the literature (26,46), EGFR mutation did not statistically impact on this parameter. It has been extensively reported that tumors with a greater mutational load could generate more neoantigens leading to a larger repertoire of tumor-specific T cells (41).…”
Section: Discussioncontrasting
confidence: 45%
“…These cells are likely responsible for IFNg secretion, the most powerful PD-L1 stimulating factor (45). Secondly, KRAS mutation was associated with a reduced expression of PD-L1, as previously documented (44), while, at variance with the literature (26,46), EGFR mutation did not statistically impact on this parameter. It has been extensively reported that tumors with a greater mutational load could generate more neoantigens leading to a larger repertoire of tumor-specific T cells (41).…”
Section: Discussioncontrasting
confidence: 45%
“…We believe that further stratification of patients on the basis of not only their tumor type but also their TIME type will yield better insight into overall survival and the likelihood of response to immunotherapeutics, and will provide vast datasets to help identify new druggable targets. This progress will be garnered by using the most cutting-edge techniques in multiparametric imaging 106 , mass cytometry 107,108 and single-cell RNA sequencing 109 . Critical to this goal is that improved resolution of cellular composition and analysis of functional status and spatial distribution must be paired with relevant patient outcomes (Fig.…”
Section: Future Directionsmentioning
confidence: 99%
“…Advances in sequencing platforms 3840 have shown us that micro-evolutionary genetic changes, including somatic mutations, copy number alterations and structural variants in the genome, alongside heritable factors, are detectable independently at both primary and secondary sites as a result of site-specific, context-dependent selective pressures 6, 33, 4143 . This has allowed the identification of hallmark mutational signatures in many different cancer types as well as their metastases 4447 and is facilitating a deeper subclassification of specific cancers 4852 .…”
Section: The Process Of Metastasismentioning
confidence: 99%